LA SOCIETÀ CONCRETA. CONSIDERAZIONI SU FICHTE E HEGEL - Fonnesu, Luca (Daimon Revista Internacional de Filosofia, 1994)
This study suggests a comparison between the social and political philosophy of Fichte and Hegel, with special attention to the problem of the existence of classes or ranks, the Stände. Both Fichte and Hegel think that the determination of the abstract juridical subject in a concrete social figure can avoid the social and ethical disorder caused by the new industrial world. Nevertheless, Fichte and Hegel give different interpretation of the concept of Stand, and of its significance for a theory of society and of State. A further important common feature -the search for a «universal class»- reveals a different conception of the relationship between State and society.